2018
DOI: 10.1002/chem.201804168
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Responses to the Three Redox Levels of Fe(NO)N2S2‐Fe(NO)2

Abstract: The nitrosylated diiron complexes, Fe (NO) , of this study are interpreted as a mono-nitrosyl Fe(NO) unit, MNIU, within an N S ligand field that serves as a metallodithiolate ligand to a dinitrosyl iron unit, DNIU. The cationic Fe(NO)N S ⋅Fe(NO) complex, 1 , of Enemark-Feltham electronic notation {Fe(NO)} -{Fe(NO) } , is readily obtained via myriad synthetic routes, and shown to be spin coupled and diamagnetic. Its singly and doubly reduced forms, {Fe(NO)} -{Fe(NO) } , 1 , and {Fe(NO)} -{Fe(NO) } , 1 , were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Spectroscopic discriminations of these different types of DNICs by EPR spectroscopy, infrared (IR) spectroscopy, Fe/S K-edge X-ray absorption near-edge spectroscopy, and 15 N NMR were reviewed elsewhere . In the following sessions, we will review the spectroscopic and computational insights into the bonding nature within the [Fe­(NO) 2 ] unit and the electronic structure of classical DNICs, whereas the study of metallothiolate-bound DNICs is reported in other literature. …”
Section: Results and Discussion: Bonding Nature And Electronic Struct...mentioning
confidence: 99%
“…Spectroscopic discriminations of these different types of DNICs by EPR spectroscopy, infrared (IR) spectroscopy, Fe/S K-edge X-ray absorption near-edge spectroscopy, and 15 N NMR were reviewed elsewhere . In the following sessions, we will review the spectroscopic and computational insights into the bonding nature within the [Fe­(NO) 2 ] unit and the electronic structure of classical DNICs, whereas the study of metallothiolate-bound DNICs is reported in other literature. …”
Section: Results and Discussion: Bonding Nature And Electronic Struct...mentioning
confidence: 99%
“… Darensbourg and coworkers developed the butterfly M­(μ-SR) 2 M’ type diiron complex 248 that mimics the [FeFe] hydrogenase active site with an AF coupled {FeNO} 7 -{Fe­(NO) 2 } 9 center, which reacts with strong acid leading to H 2 evolution . The key to success of this catalyst appears to be the coopertivity of the two iron nitrosyl units, both of which can accommodate redox changes, resulting in efficient electron transfer, storage, and proton reduction. , This particular system opened up an avenue for future exploration of different carbon backbones and different metal active sites for HER catalysts including complex 264 . , …”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
“…NO transfer between transition metals is known to be mechanistically diverse, leading, on the chemists’ benchtop, to thermodynamically controlled, self-assembly products . Such was the case in the preparation of the diiron trinitrosyl complex A , shown in the upper left corner of Figure and accessible by myriad routes. , The right-hand corner shows the neutral W­(CO) 4 derivative B , which is displayed in several neutral (N 2 S 2 )­M [N 2 S 2 = N , N -bis­(2-mercaptoethyl)-1,4-diazacycloheptane] metalloligands where M 2+ = Ni, VO, Fe­(NO), and (shown here) Co­(NO) . The CO ligands reported on the donor abilities of the metal-modified dithiolates according to ν­(CO) IR values in the stable tungsten carbonyl reference compounds .…”
Section: Introductionmentioning
confidence: 99%